Current perspectives on the software engineering process. Issue 11 (1st September 2020) - Biró, Miklós; Colomo‐Palacios, Ricardo; Messnarz, Richard
Abstract: This volume comprises a selected set of high‐quality and extended articles of the 26th Systems, Software and Services Process Improvement (EuroSPI) Conference, held during September 18–20, 2019 in Edinburgh, UK. Conferences were held in Dublin (Ireland) in 1994, in Vienna (Austria) in 1995, in Brighton (UK) in 1996, in Budapest (Hungary) in 1997, in Gothenburg (Sweden) in 1998, in Pori (Finland) in 1999, in Copenhagen (Denmark) in 2000, in Limerick (Ireland) in 2001, in Nuremberg (Germany) in 2002, in Graz (Austria) in 2003, in Trondheim (Norway) in 2004, in Budapest (Hungary) in 2005, in Joensuu (Finland) in 2006, in Potsdam (Germany) in 2007, in Dublin (Ireland) in 2008, in Alcala (Spain) in 2009, in Grenoble (France) in 2010, in Roskilde (Denmark) in 2011, in Vienna (Austria) in 2012, in Dundalk (Ireland) in 2013, in Luxembourg in 2014, in Ankara (Turkey) in 2015, in Graz (Austria) in 2016, in Ostrava (Czech Republic) in 2017, in Bilbao (Spain) in 2018, and in Edinburgh (UK) in 2019.